(untitled) (Bangladesh Journal of Animal Science, 2016)
The present experiment was conducted with 144 Shaver 579 egg laying pullets to compare their performances reared on barn and in cages for a period of 16 weeks from 25 to 40 weeks of age. Feed consumption, feed conversion (FC) and egg weight were significantly higher when reared on barn than in cages. However, hen day egg production (HDEP), egg mass, body weight, livability, albumen index, Haugh unit (HU), yolk index, shape index and egg shell thickness did not differ (P>0.05) between pullets under two different rearing systems. Soiled eggs (p<0.01) and shell breaking strength (P<0.05) were higher for the pullets reared on barn than in cages. In contrast, yolk color score (YCS) was higher (P<0.05) in eggs collected from the cage-reared pullets when compared with the eggs of pullets reared on barn. It is concluded that egg laying pullets can be reared either on barn or in cages successfully in Bangladesh condition without any adverse effect on egg production. Bang. J. Anim. Sci. 2015. 44 (3):151-156